Have FDI quantity and quality promoted the low-carbon development of science and technology parks (STPs)? The threshold effect of knowledge accumulation - Zhang, Shujing; Hu, Beibei; Zhang, Xiufeng (PloS one, 2021)
In recent times, China has emphasized five major development concepts to promote high-quality development: coordination, green, innovation, openness, and sharing. As a metamorphosis of these ideas, Chinese science and technology parks (STPs) are gathering areas of high-tech industries and represent advanced productive forces. Their greenness, openness, and innovative developments herald the future development trends of China. Based on the data of 52 STPs in China from 2011 to 2018, this study analyzes the impact of foreign direct investment (FDI) quantity and quality on the low-carbon development of the STPs. We use Hansen’s nonlinear panel threshold regression model with knowledge accumulation as the threshold variable. The results show the following: First, there are complex nonlinear relationships between FDI quantity, FDI quality, and the low-carbon development of the STPs. Second, FDI quantity has a significant positive impact on the low-carbon development of the STPs only when the level of knowledge accumulation is below a certain threshold. Beyond this threshold the effect is no longer significant. Third, FDI quality has a significant positive impact on the low-carbon development of STPs only when the level of knowledge accumulation is lower than a certain threshold; beyond which, the impact is no longer significant. These results can serve as a reference for China to effectively promote economic low-carbon growth of STPs and achieve green, open, and innovative development.